2022
DOI: 10.1007/s11030-022-10392-x
|View full text |Cite
|
Sign up to set email alerts
|

Computational prediction of the effect of mutations in the receptor-binding domain on the interaction between SARS-CoV-2 and human ACE2

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causing COVID-19 continues to mutate. Numerous studies have indicated that this viral mutation, particularly in the receptor-binding domain area, may increase the viral affinity for human angiotensin-converting enzyme 2 (hACE2), the receptor for viral entry into host cells, thereby increasing viral virulence and transmission. In this study, we investigated the binding affinity of SARS-CoV-2 variants (Delta plus, Iota, Kappa, Mu, Lambda, and C.1.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 78 publications
2
23
1
Order By: Relevance
“…The predicted docking score from HDOCK for alpha, beta, gamma, delta, omicron and wild type with hACE2 was −307.44, −343.55, −341.54, −343.88, −344.76 and −345.14 kcal/mol respectively. Previous studies have also reported that WT, delta and omicron variants have better docking scores as compared to other variants [ 62 , 63 ]. In a wide-scale analysis of the effects of mutations on RBD–hACE2 affinity, it was reported that approximately 84.3% of mutations did not alter binding affinity, whereas only 3.8% of mutations decreased the binding strength [ 64 ].…”
Section: Resultsmentioning
confidence: 98%
“…The predicted docking score from HDOCK for alpha, beta, gamma, delta, omicron and wild type with hACE2 was −307.44, −343.55, −341.54, −343.88, −344.76 and −345.14 kcal/mol respectively. Previous studies have also reported that WT, delta and omicron variants have better docking scores as compared to other variants [ 62 , 63 ]. In a wide-scale analysis of the effects of mutations on RBD–hACE2 affinity, it was reported that approximately 84.3% of mutations did not alter binding affinity, whereas only 3.8% of mutations decreased the binding strength [ 64 ].…”
Section: Resultsmentioning
confidence: 98%
“…In previous research, only the RBD domain of the spike protein was used in the analysis of binding affinity with ACE2: no MD analysis of the structure optimization ( Celik et al, 2022 ; Gan et al, 2021 ; Shah and Woo, 2021 ; Sitthiyotha and Chunsrivirot, 2021 ; Tragni et al, 2022 ) and/or local optimization of only the RBD domain of the spike protein ( Celik et al, 2022 ; Gan et al, 2021 ; Kumar et al, 2022 ; Shah and Woo, 2021 ; Sitthiyotha and Chunsrivirot, 2021 ; Tragni et al, 2022 ; Xue et al, 2021 ). However, we chose the three-dimensional structure of the complete trimeric spike protein (PDB ID: 6ZGG ) in homology modeling in this research.…”
Section: Discussionmentioning
confidence: 99%
“…In other previous research, only RBD domain of spike protein were used for the analysis of binding affinity with ACE2 as below: no MD analysis for the structure optimization [22][23][24][25][26] and/or local optimization of only RBD domain [22][23][24][25][26][27][28] of spike protein. However, we choose 3-D structure of whole trimer spike protein (PDB ID: 6ZGG) for homology modeling in this research.…”
Section: Discussionmentioning
confidence: 99%
“…In previous research, only the RBD domain of the spike protein was used in the analysis of binding affinity with ACE2: no MD analysis of the structure optimization [22][23][24][25][26] and/or local optimization of only the RBD domain [22][23][24][25][26][27][28] of the spike protein.…”
Section: Discussionmentioning
confidence: 99%